Velvet bean roots stimulates humoral and cell mediated immunity and offers protection against Cyclophosphamide induced myelosuppression. - Krishna Murthy,; S H Mishra, (International Journal of Phytomedicine, 2016)
The objective of the study was to investigate the immunomodulatory activity of roots of Mucuna pruriens on cellular and humoral immunity. Extraction and phytochemical screening of the roots were performed using standard methods, HPTLC fingerprinting profiles of the methanol extract were developed on CAMAG system, to resolve components, Quantification of β-Sitosterol was done by validated HPTLC method. Immunomodulatory activity of the extract was assessed by Cyclophosphamide-induced myelosuppression assay, Macrophage phagocytosis by Carbon clearance method, Humoral antibody response and Delayed type hypersensitivity reaction using SRBC as an antigen. Oral administration of methanolic extract of Mucuna roots at 100, 200 and 400 mg/kg in mice dose dependently potentiated the delayed-type hypersensitivity reaction induced by sheep red blood cells. It significantly enhanced the circulating antibody titre in response to SRBC and macrophage phagocytosis. Cyclophosphamide induced myelosuppression was counteracted in a dose dependent manner with increase in the levels of WBC compared to cyclophosphamide group. The results of the present study suggests that the developed HPTLC fingerprint profiles of the major constituents in methanolic extract along with their Rf values would serve as a reference standard, methods developed for the quantification of L-dopa and β-Sitosterol can be used to ensure the identity and quality of the plant and the results of the biological studies indicates that the roots of Mucuna pruriens influenced both humoral and cell mediated immunity and offered protection against immunosuppression induced by cytotoxic agent Cyclophosphamide holds promise as an immunomodulator.